2008
DOI: 10.1016/j.cmet.2008.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Opposing Effects of Dietary Protein and Sugar Regulate a Transcriptional Target of Drosophila Insulin-like Peptide Signaling

Abstract: Specific neurosecretory cells of the Drosophila brain express insulin-like peptides (dilps), which regulate growth, glucose homeostasis, and aging. Through microarray analysis of flies in which the insulin-producing cells (IPCs) were ablated, we identified a target gene, target of brain insulin (tobi), that encodes an evolutionarily conserved alpha-glucosidase. Flies with lowered tobi levels are viable, whereas tobi overexpression causes severe growth defects and a decrease in body glycogen. Interestingly, tob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
188
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 163 publications
(208 citation statements)
references
References 38 publications
20
188
0
Order By: Relevance
“…This finding is consistent with our general knowledge that insulin signaling is rapidly modulated in response to changes in nutrition in animals, including Drosophila (26,27). The fact that the feeding activities of GS1189 larvae continuously remained very low suggested that regulation of feeding potencies by insulin signaling was somehow disordered in the mutant animals.…”
Section: Discussionsupporting
confidence: 80%
“…This finding is consistent with our general knowledge that insulin signaling is rapidly modulated in response to changes in nutrition in animals, including Drosophila (26,27). The fact that the feeding activities of GS1189 larvae continuously remained very low suggested that regulation of feeding potencies by insulin signaling was somehow disordered in the mutant animals.…”
Section: Discussionsupporting
confidence: 80%
“…2A). As expected, this group also included known downstream targets of IIS, for example the target of brain insulin (tobi) (40). These results were confirmed independently for selected genes by RT-PCR (Fig.…”
Section: Iis In Oenocytes Is Crucial To Maintain Starvation Resistancsupporting
confidence: 66%
“…However, a role of AKH in AMPK activation, which would establish an autoregulatory loop, has not been addressed. Similarly, up-regulation of Akh on the transcriptional level in response to loss of insulin signaling has been described in Drosophila (Buch et al 2008). But again, it is unclear whether this antagonistic regulation involves an autoregulatory mechanism.…”
Section: Autoregulation Of the Akh Genementioning
confidence: 99%